Confined Amorphous Red Phosphorus in MOF‐Derived N‐Doped Microporous Carbon as a Superior Anode for Sodium‐Ion Battery. Issue 16 (22nd February 2017) - Li, Weihan; Hu, Shuhe; Luo, Xiangyu; Li, Zhongling; Sun, Xizhen; Li, Minsi; Liu, Fanfan; Yu, Yan
Abstract : Red phosphorus (P) has attracted intense attention as promising anode material for high‐energy density sodium‐ion batteries (NIBs), owing to its high sodium storage theoretical capacity (2595 mAh g −1 ). Nevertheless, natural insulating property and large volume variation of red P during cycling result in extremely low electrochemical activity, leading to poor electrochemical performance. Herein, the authors demonstrate a rational strategy to improve sodium storage performance of red P by confining nanosized amorphous red P into zeolitic imidazolate framework‐8 (ZIF‐8) ‐derived nitrogen‐doped microporous carbon matrix (denoted as P@N‐MPC). When used as anode for NIBs, the P@N‐MPC composite displays a high reversible specific capacity of ≈600 mAh g −1 at 0.15 A g −1 and improved rate capacity (≈450 mAh g −1 at 1 A g −1 after 1000 cycles with an extremely low capacity fading rate of 0.02% per cycle). The superior sodium storage performance of the P@N‐MPC is mainly attributed to the novel structure. The N‐doped porous carbon with sub‐1 nm micropore facilitates the rapid diffusion of organic electrolyte ions and improves the conductivity of the encapsulated red P. Furthermore, the porous carbon matrix can buffer the volume change of red P during repeat sodiation/desodiation process, keeping the structure intact after long cycle life. Abstract : By confining nanosized amorphous (red P) into a zeolitic imidazolate framework‐8 (ZIF‐8)‐derived nitrogen‐doped microporous carbon matrix (denoted as P@N‐MPC), the sodium‐storage performance of red P is improved significantly. The superior sodium‐storage performance is mainly attributed to the novel nanosized core/shell structure. The P@N‐MPC holds great promise for practical application in next‐generation high‐energy‐density sodium‐ion batteries.